Study design, general characteristics of participants, and preliminary findings from the metabolome, microbiome, and dietary salt intervention study (MetaSalt). Issue 4 (1st December 2021) - Ruan, Zengliang; Li, Jianxin; Liu, Fangchao; Cao, Jie; Chen, Shufeng; Chen, Jichun; Huang, Keyong; Wang, Yaqin; Li, Hongfan; Wang, Yan; Xue, Zhongyu; Wang, Laiyuan; et al.
Abstract: Background: High sodium intake is an important risk factor for hypertension and cardiovascular disease. However, the association between gut microbiota composition and metabolomic profiles with dietary sodium intake and blood pressure (BP) is not well‐understood. The metabolome, microbiome, and dietary salt intervention (MetaSalt) study aimed to investigate microbial and metabolomic profiles related to dietary sodium intake and BP regulation. Methods: This family‐based intervention study was conducted in four communities across three provinces in rural northern China in 2019. Probands with untreated prehypertension or stage‐1 hypertension were identified through community‐based BP screening, and family members including siblings, offspring, spouses, and parents were subsequently included. All participants participated in a 3‐day baseline examination with usual diet consumption, followed by a 10‐day low‐salt diet (3 g/d of salt or 51.3 mmol/d of sodium) and a 10‐day high‐salt diet (18 g/d of salt or 307.8 mmol/d of sodium). Differences in mean BP levels were compared according to the intervention phases using a paired Student's t‐test. Results: A total of 528 participants were included in this study, with a mean age of 48.1 years, 36.7% of whom were male, 76.8% had a middle school (69.7%) or higher (7.1%) diploma, 23.4% had a history of smoking, and 24.4% were current drinkers. The mean arterial pressure at baseline was 97.2 ± 10.5 mm Hg for all participants, and significantly decreased during the low‐salt intervention (93.8 ± 9.3, P < 0.0001) and subsequently increased during the high‐salt intervention (96.4 ± 10.0, P < 0.0001). Conclusions: Our dietary salt intervention study has successfully recruited participants and will facilitate to evaluate the effects of gut microbiota and metabolites on BP regulation in response to sodium burden, which will provide important evidence for investigating the underlying mechanisms in the development of hypertension and subsequent cardiovascular diseases. Trial registration: The study was registered in the Chinese Clinical Trial Registry database (ChiCTR1900025171).